The impact of response kinetics for multiple myeloma in the era of novel agents - Yan, Yuting (Blood Adv, 2019)
Rapid remission by induction therapy has long been recognized as an important predictor for long-time survival in acute leukemia. However, the impact of response kinetics on multiple myeloma (MM) seems to be different and remains unexplored. The relationship between response kinetics and outcome were assessed in 626 patients with newly diagnosed MM who were included in a prospective, nonrandomized clinical trial (BDH 2008/02). Patients were assigned to either immunomodulatory drug- or proteasome inhibitor–based therapy. The response depth, time to best response (T(BR)) and duration of best response (D(BR)) were collected. Depth of response was associated with superior outcomes, consistent with findings from other studies. However, the early responders (defined as T(BR) ≤3 months) showed significantly worse survival compared with late responders. We found that patients with rapid complete remission experienced inferior survivals comparable to those attaining a gradual partial remission. Moreover, 4 distinct response kinetics patterns were identified. Patients with gradual and sustained remission (“U-valley” pattern) experienced superior outcomes, whereas poor outcomes were observed in rapid and transient responders (“roller coaster” pattern) (median overall survival, 126 vs 30 months). The effects of response patterns on survival were confirmed in patients at different stages of disease and cytogenetic risk, including transplant-eligible patients and those attaining different extents of response depth. Collectively, our data indicated that slow and gradual response is a favorable prognostic factor in MM. In addition to response depth, the kinetic pattern of response is a simple and powerful predictor for survival even in the era of novel agents.